2015
DOI: 10.3389/fnana.2015.00040
|View full text |Cite
|
Sign up to set email alerts
|

Whole-brain mapping of the direct inputs and axonal projections of POMC and AgRP neurons

Abstract: Pro-opiomelanocortin (POMC) neurons in the arcuate nucleus (ARC) of the hypothalamus and nucleus tractus solitarius (NTS) of the brainstem play important roles in suppressing food intake and maintaining energy homeostasis. Previous tract-tracing studies have revealed the axonal connection patterns of these two brain areas, but the intermingling of POMC neurons with other neuron types has made it challenging to precisely identify the inputs and outputs of POMC neurons. In this study, we used the modified rabies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
240
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(270 citation statements)
references
References 74 publications
(103 reference statements)
12
240
1
3
Order By: Relevance
“…For instance, apart from its important role in stress regulation (Fekete and Lechan 2014), the Pa is also part of a neuronal circuitry that regulates food intake. The best-characterized neurochemical pathways related to energy consumption and food intake are the orexigenic neuropeptide Y/ Agouti-related protein and the anorexigenic proopiomelanocortin/cocaine-and amphetaminerelated transcript neurons in the Arc (Wang et al 2015), which also showed increases in Fos-ir in the present study. These neurons project from the Arc to other key hypothalamic nuclei, such as the Pa and the VMH (Kotagale et al 2014).…”
Section: Discussionsupporting
confidence: 66%
“…For instance, apart from its important role in stress regulation (Fekete and Lechan 2014), the Pa is also part of a neuronal circuitry that regulates food intake. The best-characterized neurochemical pathways related to energy consumption and food intake are the orexigenic neuropeptide Y/ Agouti-related protein and the anorexigenic proopiomelanocortin/cocaine-and amphetaminerelated transcript neurons in the Arc (Wang et al 2015), which also showed increases in Fos-ir in the present study. These neurons project from the Arc to other key hypothalamic nuclei, such as the Pa and the VMH (Kotagale et al 2014).…”
Section: Discussionsupporting
confidence: 66%
“…This fact clearly needs to be considered in our analysis. However, a recent elegant study, employing a dual viral vector tracing strategy, reported that POMC neurons in the Arc and Sol give rise to a very different set of axonal projections (Wang et al, 2015). Thus, axons from Sol POMC neurons were found to be mainly distributed in the caudal brainstem, although some Sol axons were additionally observed in rostral brain areas, including the hypothalamus (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…However, a recent elegant study, employing a dual viral vector tracing strategy, reported that POMC neurons in the Arc and Sol give rise to a very different set of axonal projections (Wang et al, 2015). Thus, axons from Sol POMC neurons were found to be mainly distributed in the caudal brainstem, although some Sol axons were additionally observed in rostral brain areas, including the hypothalamus (Wang et al, 2015). On the other hand, in line with the present findings, the heaviest projections of Arc POMC neurons were found in the hypothalamus with a minor contingent innervating the mid-and hindbrain (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There are several subtypes of the melanocortin peptides, such as adrenocorticotrophin (ACTH) and alpha-melanocyte-stimulating hormone (α-MSH), which act at G-protein-coupled melanocortin receptors such as the MC 1-5 receptors [118,138,139]. In the brain, POMC is mainly expressed in the Arc [138,140], and projects to various regions of the hypothalamus [118,141]. Certain POMC gene mutations may contribute to obesity in healthy human populations [142,143], while mouse knockout for POMC also shows the obese phenotype [138,144].…”
Section: The Role Of Pomc and Cart In Sga-induced Weight Gainmentioning
confidence: 99%